2023
DOI: 10.1128/spectrum.01378-22
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Diagnostic Performance of Droplet Digital PCR for Suspected Bloodstream Infections

Abstract: ddPCR is a promising method to address the current challenges of BSI diagnosis and precise treatment, as it is highly efficient in DNA detection. It shortens the identification of BSI-related pathogens from several days of traditional bacterial culture to 4 to 5 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…Most recently, a very few clinical trials had suggested that the ddPCR may facilitate precision antimicrobial stewardship by dynamic monitoring pathogens [29,30]. In line with these reports, the enrolled patients' condition steadily improved following the clinical escalation of antibiotics, and the load of pathogens and drug resistance genes signi cantly decreased, according to drug resistance gene detection at the same time.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Most recently, a very few clinical trials had suggested that the ddPCR may facilitate precision antimicrobial stewardship by dynamic monitoring pathogens [29,30]. In line with these reports, the enrolled patients' condition steadily improved following the clinical escalation of antibiotics, and the load of pathogens and drug resistance genes signi cantly decreased, according to drug resistance gene detection at the same time.…”
Section: Discussionmentioning
confidence: 73%
“…It has been utilized in several medical applications, including liquid biopsy for cancer monitoring, rejection monitoring following organ transplantation and study of prenatal genetic disorders [24][25][26]. Till now, a few reports had documented that ddPCR had been utilized to detect bacterial infections in septic patients or patients with a highly suspected BSI in the intensive care units (ICU) [27][28][29][30][31], which had shown advantages in identifying polymicrobial BSIs and ability to dynamically monitor changes in pathogenic microorganisms in the blood, therefore might be used to evaluate antibiotic e cacy and survival prognosis. As we all know, the intensive care populations mainly with septic shock are to some extent different from a general ED population of patients with varying severity of disease and with relatively lower mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a possibility that pathogens may not be detected because mNGS is unable to detect trace amounts of nucleic acid in the blood. A study on bloodstream infections has shown that the detection rate of ddPCR within the detection range of ddPCR targets is significantly higher than that of mNGS [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The droplets were loaded into an iScanner to measure the fluorescence signals of 5 different droplets (FAM, VIC, ROX, CY5, and A425) (Pilot Gene Technology Co., Ltd., Hangzhou, China). The minimum detection limit is 0.7 copies/ul [ 6 ]. The entire process took 3.5 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation